STRATEGI MENINGKATKAN KEPATUHAN ETIKA AKADEMIK MAHASISWA DALAM DISKUSI KELAS - Rinanda Fasya; Maimunah; Madinah Marwah; Fauzan Ghofur Marbun, Muhammad; Muis, Ilham (CV. Arsy Persada Quality, 2025)
Academic ethics compliance is a fundamental aspect in higher education that is not only related to academic honesty, but also affects the quality of intellectual interactions, including in class discussions. This study aims to determine strategies to improve students' academic ethics compliance in class discussions by analyzing the roles of education, lecturers, technology, and academic culture. The results of the study indicate that students' academic ethics compliance can be improved through systematic and continuous education, the role of lecturers as role models, the use of technology to monitor and supervise student activities, and the formation of a positive academic culture. Thus, students' academic ethics compliance in class discussions can be improved and create a positive and productive academic environment, thereby improving the quality of learning and achieving academic goals more effectively.